Nurse Workloads Affecting Negative on Patient Safety in Hospital (Case Study at X Hospital) - Mersy Delty Kainama; Ratna Indrawati; Rina Mutiara (Universitas Muhammadiyah Yogyakarta, 2020)
Patient safety is a serious global health problem. The results showed that in developed countries one in ten patients who get injured during treatment in the hospital. Developing countries, patients who are harmed during the hospitalization process are likely to be more likely than those in developed countries. Based on the results of the 2018 evaluation at RSIA Bunda Aliyah, it shows that compliance with the risk of injury due to a patient falling in the inpatient department reaches 99% of the 100% standard, where only 1% is still a problem in preventing the risk of falling. Compliance in hand washing was 65.3% with a standard of 85%, the data also showed that patient and family satisfaction reached 70.9% with a standard of 80%. The purpose of this study was to analyze the effect of nurses' workload on the implementation of patient safety at RSIA Bunda Aliyah with service quality as an intervening variable. The method used in this research is multiple regression path analysis, which was conducted on 74 respondents. The results of this study indicate that there is a significant influence between the workload of nurses on patient safety, but service quality cannot be an intervening variable on both variables and service quality does not have a significant effect on patient safety. The results showed that the dominant influence was the workload of nurses on patient safety. Where the significant value of workload and service quality for patient safety is P = 0.044, workload on patient safety is P = 0.012, workload on service quality is P = 0.019, and service quality for patient